Atypical Central Neurocytoma with Recurrent Spinal Dissemination over a Period of 20 Years: A Case Report and Review of the Literature. (9th June 2013) - Juratli, Tareq A.; Geiger, Kathrin; Leimert, Mario; Schackert, Gabriele; Kirsch, Matthias
Abstract : We present an unusual case of a late recurrent central neurocytoma that was rediagnosed as an ependymoma and neurocytoma in accordance with changes in histological classifications. Case Description . A 56-year-old male teacher presented with incomplete transverse syndrome due to several intradural extramedullary tumors at the level of lumbar vertebrae 1–3. The histological diagnosis at the time was atypical ependymoma. One year later, two additional tumors were removed at the L5-S1 vertebral level. For 12 years, the patient remained tumor free on followup. Fourteen years after the initial diagnosis, the patient presented with thoracic paresthesias due to two new extramedullary tumors in the C7-T1 and the T8-T9 vertebral levels. After complete removal of the tumors, a radiological survey revealed an intracranial lesion in the third ventricle. Five months later, an additional lesion recurrence was removed surgically. The most recent histological diagnosis revealed an atypical central neurocytoma. In retrospect, the previous tumors were reclassified as neurocytoma according to the additional immunohistochemistry evidence. Discussion . There is no standard adjuvant treatment regimen for atypical neurocytoma; therefore, the patient is currently under close followup. Modern histopathological diagnosis is essential in these cases. Potential routes for dissemination of the tumor should be considered upon first recurrence.